Konsumsi Gula Tambahan Menurunkan Asupan Zat Besi dan Seng pada Anak Usia 24-59 Bulan di Jawa Tengah: Konsumsi Gula Tambahan Menurunkan Asupan Zat Besi dan Seng pada Anak Usia 24-59 Bulan di Jawa Tengah - Aila, Safrina Luthfia; Dieny, Fillah Fithra; Candra, Aryu; Wijayanti, Hartanti Sandi (Universitas Airlangga, 2023)
Background: High sugar consumption was found among children in Indonesia. Excessive intake of added sugars was predicted to cause micronutrient dilution, a negative potential effect compromising micronutrient intake such as iron and zinc. Objectives: This study examined the association between added sugar consumption and iron and zinc intake among children aged 24-59 months. Methods: This study was a secondary data analysis of the 2014 Total Diet Study in Central Java Province. The subjects were 394 children aged 24-59 months. Dietary intake and sociodemographic data were assessed using the 24-hour food recall and household questionnaire. Added sugars consumption was classified into six cut-offs based on its contribution to daily energy (%E), namely: C1 (<5%E), C2 (5%E - <10%E), C3 (10%E - <15%E), C4 (15%E - <20%E), C5 (20%E - 25%E), and C6 (>25%E). Results: 48% of subjects had added sugar intake exceeding the WHO recommendation. Subjects with iron and zinc intake below the Estimated Average Requirement (EAR) were 15.2% and 24.1%, respectively. As the added sugar consumption increased, iron and zinc intake decreased significantly (p<0.05). This study found a significant decrease in the intake of iron occurred at added sugar consumption â‰¥20%E (C5 and above) while decreasing the intake of zinc at added sugar consumption â‰¥15%E (C4 and above) (p<0,05). Conclusions: Added sugar consumption had an inverse association with iron and zinc intake among children aged 24-59 months, which showed the occurrence of micronutrient dilution.